2022
DOI: 10.3390/en15218067
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Studies of Smart Distributed Energy Resources along with Energy Blockchain

Abstract: This article studies the broad methodology and major application of smart distributed energy resources (DER) in terms of energy generation, consumption, transaction, and power scheduling. This article simplifies a general DER system into a generic type of integrated DER model. This model is used to investigate a smart DER system that transforms three input parameters, (3I parameters) into three critical output functions(3O functions); hence, the model is also called the 3I3O model. The power at a common connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…When looking at how to develop the optimal transaction strategy for market entities remains to be further research, Jin et al (2022) design a differentiated optimal matching Blockchain excess trading with game theory strategy for energy consumers and producers, which can help energy users match the optimal transaction object and promote the consumption of nearby renewable energy. Bokkisam et al (2022) propose a P2P transaction method between prosumers and consumers with excess energy.…”
Section: Related Workmentioning
confidence: 99%
“…When looking at how to develop the optimal transaction strategy for market entities remains to be further research, Jin et al (2022) design a differentiated optimal matching Blockchain excess trading with game theory strategy for energy consumers and producers, which can help energy users match the optimal transaction object and promote the consumption of nearby renewable energy. Bokkisam et al (2022) propose a P2P transaction method between prosumers and consumers with excess energy.…”
Section: Related Workmentioning
confidence: 99%
“…Many researchers have discovered various scientific phenomena/data, and many studies have been reported [48][49][50][51][52][53][54] . Researchers have conducted investigations and have expanded the knowledge on this subject by referring to the results in the literature [55][56][57][58][59] .…”
Section: Energy Blockchainmentioning
confidence: 99%